Bentuk Pengaturan Kewenangan Kepala Desa Dalam Mencegah Konflik Pertanahan Ditinjau Dari Asas Kepastian Hukum - Chris Januardi (Fakultas Hukum Universitas Islam Malang, 2023)
The village community in resolving land conflicts prefers conflict resolution through the village head. However, there is a blurring of norms in the regulations governing the settlement of disputes between village communities by the Village Head because they do not regulate the implementation of case settlements. This research uses a type of normative juridical research, using statutory and conceptual approaches. Legal materials were analyzed using descriptive, evaluative, and argumentative methods. The village head's authority in preventing land conflicts is contained in Law Number 6 of 2014 concerning Villages and Law Number 23 of 2014 concerning Regional Government. The forms of prevention that can be carried out by the village head in preventing land conflicts are controlling land administration from sources of conflict, proactive actions, legal counseling, fostering community participation and empowerment, and mapping conflict-prone lands.